2010
DOI: 10.1016/j.cell.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide Identification of RNA-Binding Protein and MicroRNA Target Sites by PAR-CLIP

Abstract: Summary RNA transcripts are subject to post-transcriptional gene regulation involving hundreds of RNA-binding proteins (RBPs) and microRNA-containing ribonucleoprotein complexes (miRNPs) expressed in a cell-type dependent fashion. We developed a cell-based crosslinking approach to determine at high resolution and transcriptome-wide the binding sites of cellular RBPs and miRNPs. The crosslinked sites are revealed by thymidine to cytidine transitions in the cDNAs prepared from immunopurified RNPs of 4-thiouridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

169
3,071
12
19

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,651 publications
(3,303 citation statements)
references
References 71 publications
169
3,071
12
19
Order By: Relevance
“…Our data indicate that Pdcd4 targets a 'Pdcd4-response element' that maps to the coding region of c-myb mRNA. At first glance, it appears unusual that the coding region of an mRNA is the target of a translational regulatory mechanism; however, genome-wide analyses of interactions of regulatory RNA-binding proteins with mRNAs have revealed surprisingly large numbers of interactions that take place in the coding regions of the cognate mRNAs (Hogan et al, 2008;Hafner et al, 2010). Previous studies have also identified specific regulatory proteins that bind to the coding regions of certain mRNAs, such as the thymidylate synthase and dihydrofolate reductase, both of which bind to the coding regions of their own mRNAs (Ercikan-Abali et al, 1997;Lin et al, 2000;Zhang et al, 2010) and the RNA-binding protein HuR, which interacts with the coding region of CD83 RNA (Prechtel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that Pdcd4 targets a 'Pdcd4-response element' that maps to the coding region of c-myb mRNA. At first glance, it appears unusual that the coding region of an mRNA is the target of a translational regulatory mechanism; however, genome-wide analyses of interactions of regulatory RNA-binding proteins with mRNAs have revealed surprisingly large numbers of interactions that take place in the coding regions of the cognate mRNAs (Hogan et al, 2008;Hafner et al, 2010). Previous studies have also identified specific regulatory proteins that bind to the coding regions of certain mRNAs, such as the thymidylate synthase and dihydrofolate reductase, both of which bind to the coding regions of their own mRNAs (Ercikan-Abali et al, 1997;Lin et al, 2000;Zhang et al, 2010) and the RNA-binding protein HuR, which interacts with the coding region of CD83 RNA (Prechtel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of combinatorial targeting of genes by multiple miRNAs has not been well studied in vivo however the advent of new methodologies including CRISPR/Cas9 site-directed mutagenesis and crosslinkingimmunoprecipitation (CLIP) protocols can now expedite the identification of biologically relevant cis and trans sequences [15] [16]. In addition to improving our understanding miRNA target recognition, these protocols have the potential of establishing the functional importance of low expressed sequences either by loss of function studies or by identifying robust miRNA : target gene interactions.…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…Since these early model studies, the TargetScan algorithm has continued to refine its target predictions and remains among the most recognized in the field [22]. Recent reports have implemented biochemical approaches (crosslinking and immunoprecipitation, CLIP) to identify specific miRNA target sites by isolating and sequencing the 3'UTR region bound by Ago proteins [16]. While these protocols are currently dependent upon large quantities of source tissue material in cell culture, this limitation excludes the possibility of studying human islets however the development of the stem cell differentiation protocols may make the CLIP protocol viable for human β-cells in the near future.…”
Section: Identification Of Microrna Targets In the β-Cellmentioning
confidence: 99%
“…Hence, it becomes important to understand the structural and functional characteristics of RBPs in humans. Increasing interest in RBPs has led to the development of various experimental protocols like SELEX (systematic evolution of ligands by exponential enrichment) [9,10], CLIP [11], PAR-CLIP [12,13], iCLIP [14] and RNA compete [15], to identify the binding specificities of RBPs; thus adding context and dynamics to the regulation of gene expression at post-transcriptional level.…”
Section: Introductionmentioning
confidence: 99%